Non-Chinese Indonesian Through The Eyes of 1998 Victim - William Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
In 1998, a massive riot happened in Jakarta which is known as the 1998 tragedy. Lots of Chinese Indonesian people house and shops were burned, they were also raped in front of their families, some of them were burned after being raped. In the end, Chinese Indonesians people were slowly being accepted by society as their culture and national holidays were acknowledged. However, the tragedy still remains unforgettable to Chinese Indonesian people. Thus, this research is conducted to find out what Chinese Indonesians who experience the 1998 tragedy think of non-Chinese people after 23 years of the tragedy and why they think so. The finding of the study, show that Chinese indonesia still think of non Chinese people in a good way and believe that they still have good relationship with them. Although they show symptom of being traumatize, it doesn’t change how they view non Chinese people.Key word: Chinese Indonesians, Tragedy 1998, Traumatic experience, Soeharto.